2011
DOI: 10.1007/s10965-011-9750-z
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition behavior and mechanical properties of elastomeric composites based on polyolefinic thermoplastic elastomer and organomontmorillonite

Abstract: The elastomeric composites based on organomontmorillonite (OMMT) and Santoprene thermoplastic elastomer were prepared by melt processing. Maleic anhydride grafted polypropylene (PP-g-MA) was used as a compatibilizer for the composite system. By adding optimum content of PP-g-MA, the fracture surface of the composites observed by SEM was smoothened as a result from compatibilizing effect. From XRD results, the measured d-spacing data proved a good dispersion of nanoclay along with compatibilizer. Thermal decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In the recent decades, TPV/inorganic nanocomposites have been widely studied to enhance material properties of the TPV. TPV based on polypropylene (PP)/ethylene‐propylene‐diene monomer (EPDM) blend reinforced with several nanofillers such as organoclay,2–7 silica,8, 9 graphite and its derivatives,10, 11 and bohemite alumina12 was reported. Effects of type of nanofillers, compatibilizers, and vulcanization systems on material properties of the nanocomposites were investigated in the studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent decades, TPV/inorganic nanocomposites have been widely studied to enhance material properties of the TPV. TPV based on polypropylene (PP)/ethylene‐propylene‐diene monomer (EPDM) blend reinforced with several nanofillers such as organoclay,2–7 silica,8, 9 graphite and its derivatives,10, 11 and bohemite alumina12 was reported. Effects of type of nanofillers, compatibilizers, and vulcanization systems on material properties of the nanocomposites were investigated in the studies.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on TPV/clay nanocomposites (TPVCN) have been widely reported in literature . Nanostructured TPVCN can be fabricated by melt mixing method using proper modification of nanofillers and matrix polymers to impart sufficient thermodynamic compatibility between them.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, TPVCN is successfully employed in diverse applications such as electrical, construction, healthcare, packaging, and many more fields. The literature review revealed that some published papers are dedicated to the polypropylene/ethylene propylene diene monomer rubber (PP/EPDM), and ethylene vinyl acetate/natural rubber ((EVA/NR) blends based TPVCN.…”
Section: Introductionmentioning
confidence: 99%